Procalcitonin‐guided protocol decreased the antibiotic use in paediatric patients with severe bronchiolitis. (4th February 2020) - Alejandre, Carme; Balaguer, Mònica; Guitart, Carmina; Torrús, Isabel; Felipe, Aida; Launes, Cristian; Cambra, Francisco José; Jordan, Iolanda
Abstract: Aim: Our aim was to determine the effectiveness and safety of a procalcitonin‐guided protocol to decrease antibiotic use in infants with severe bronchiolitis. Methods: This prospective, observational study was conducted at the Hospital Sant Joan de Déu from 2010 to 2017. Patients under the age of one were included if they were diagnosed with bronchiolitis, had a suspected bacterial infection and were admitted to the paediatric intensive care unit. A procalcitonin‐guided protocol was established in 2014, and two cohorts were compared before and after implementation: 340 in 2010‐2014 and 366 in 2015‐2017. Results: We recruited 706 patients (58.6% male) with a median age of 47 days and an interquartile range of 25.0‐100.2. The rate for antibiotic use was 79.9%, and this differed before and after implementation (88.2% vs 72.1%, P = .003). Antibiotic stewardship and withdrawal decisions were higher after implementation (22.3% vs 36.4%, P = .005). The length of antibiotic treatment was also different between the two periods (8.65 ± 4.8 days vs 5.05 ± 3.18 days, P = .023). No adverse outcomes were observed due to the implementation of the protocol. Conclusion: The implementation of a procalcitonin‐guided protocol seems to lead to a safe and general decrease in antibiotic use in paediatric patients with severe bronchiolitis.